Efficacy and Safety of Chinese Patent Medicine Combined With Oseltamivir in Treatment of Children With Influenza: A meta-Analysis - Duan, Nai-fan; Liu, Bin; Li, Xiao-na; Xiong, Yi-bai; Zhang, Yan; Zhang, Chi; LI, Li; Lu, Cheng; Lyu, Jueni (Frontiers in Pharmacology, 2021)
Background: Recently, Chinese patent medicines (CPMs) have been widely used to treat children with influenza in China, with curative effects. Therefore, the efficacy and safety of such treatment require further evaluation. The present meta-analysis integrated data from several independent studies to determine overall treatment trends in children with influenza. Methods: The following databases were searched for randomized controlled trials (RCTs) published from their inception to December 12, 2020: CNKI, Wanfang, SinoMed, PubMed, Cochrane library, and Embase. Two researchers independently extracted the data, assessed the methodological quality of the studies, and conducted a meta-analysis of the results using Review Manager 5.2. The results were assessed using forest plots, and publication bias was evaluated using a funnel plot. Results: A total of 21 RCTs involving 2960 cases were included. Compared to oseltamivir alone, CPMs combined with oseltamivir reduced the duration of symptoms, including that of fever (mean difference [MD] = −0.64, 95% confidence interval [CI]: −0.86 to −0.41, P < 0.00001), cough (MD = −0.82, 95% CI: −1.02 to −0.62, P < 0.00001), nasal obstruction (MD = −0.88, 95% CI: −1.15 to −0.61, P < 0.00001), and sore throat (MD = −0.92, 95% CI: −1.26 to −0.57, P < 0.00001). Combined therapy also reduced the time of viral shedding (MD = −0.53, 95% CI: −0.70 to −0.36, P < 0.00001) and the occurrence of adverse drug reactions (ADRs) (RR=0.53, 95% CI: 0.34 to 0.83, P = 0.005). Conclusions: CPMs combined with oseltamivir reduced the duration of symptoms, shortened the time of viral shedding, and reduced the number of ADRs. However, these results should be considered with caution because there was marked heterogeneity and publication bias in the research data. More rigorous RCTs should be designed to verify the effect of CPMs in children with influenza.